Development of SMART technology in the digital education environment of Kazakhstan (Journal of Educational Sciences, 2024)
The aim of the study is to analyze the research of Kazakhstani and foreign scientists on the development of SMART education and its digital transformation in Kazakhstan. The article analyzes the most informative scientific articles of Kazakhstani and foreign scientists devoted to the study of the state, practical application and further use of SMART technology both in the Republic of Kazakhstan in general and in the country's education system. The study examines and analyzes reliable academic databases such as Google Scholar, ERIC, Web of Science and SCOPUS, as well as relevant literature using government documents and materials from international conferences to study the main issues of digitalization in Kazakhstan. Mainly, the depth of publications for the past 5 years is taken. Based on the study of these works, the authors came to the conclusion that new digital technologies began to be actively introduced in Kazakhstan since 2018, after the adoption of the state program "Digital Kazakhstan" in December 2017. However, to date, Kazakhstan continues to lag behind many leading countries in the world in the implementation and application of new digital technologies. This allowed the authors to offer a number of recommendations that can significantly speed up this process and become one of the leading states in the digital era. The recommendations presented can help students, teachers and stakeholders effectively integrate digital technologies into the education system. The authors focused on expanding the use of SMART technology in the education system of Kazakhstan.Key words: Digital Technology, "Digital Kazakhstan", digital educational environment, SMART education,  students.